Membangun Orientasi Kewirausahaan Untuk Meningkatkan Kinerja UKM - KALVIN SINE (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
The purpose of this paper is to examine the effect of entrepreneurial orientation (EO) on SMEs’ performance. The data were collected from 170 respondents from SMEs in furniture industry located in Klender and Cirebon. The results reveal that entrepreneurial orientation affect SMEs’ performance. The results also show that the degree of EO is approximately the same across all SMEs in both locations. Similar to this, the results found there is no evidence that the degree of EO is different for exporter SMEs and non-exporter SMEs. However, exporter SMEs has better performance compare to their no-exporter counterparts.